2018
DOI: 10.1101/378588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radial Glia cell infection byToxoplasma gondiidisrupts brain microvascular endothelial cell integrity

Abstract: Congenital toxoplasmosis is a parasitic disease that occurs due vertical transmission of the protozoan Toxoplasma gondii (T. gondii) during pregnancy. The parasite crosses the placental barrier and reaches the developing brain, infecting progenitor, glial, neuronal and vascular cell types. Although the role of Radial glia (RG) neural stem cells in the development of the brain vasculature has been recently investigated, the impact of T. gondii infection in these events is not yet understood. Herein, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 83 publications
(117 reference statements)
1
2
0
Order By: Relevance
“…However, our data indicate that infected C2C12 cells display reduced TGF-β1 secretion. This behavior was also observed by our group after T. gondii infection of neural progenitors (Adesse et al, 2018). Regarding muscle cells, Swierzy et al (2014) previously demonstrated T. gondii infection effects on the TGF-β mRNA expression of myoblasts and myotubes.…”
Section: Discussionsupporting
confidence: 84%
“…However, our data indicate that infected C2C12 cells display reduced TGF-β1 secretion. This behavior was also observed by our group after T. gondii infection of neural progenitors (Adesse et al, 2018). Regarding muscle cells, Swierzy et al (2014) previously demonstrated T. gondii infection effects on the TGF-β mRNA expression of myoblasts and myotubes.…”
Section: Discussionsupporting
confidence: 84%
“…One recent study reported on the prevalence of T. gondii in a series of human autopsy samples, and the authors stated that T. gondii was detected in the neurons and astrocytes in the brains of these toxoplasmosis patients [37], findings consistent with our data. Regarding radial glial cells, one report demonstrated that T. gondii can infect rodent radial glial cells [38]; however, the considerable differences between humans and other species is notable. To date, it is not known whether human radial glial cells are susceptible to T. gondii.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelium is responsible for keeping vascular tone and controlling oxidative stress by releasing mediators such as nitric oxide (NO), endothelin, and prostacyclin and regulating angiotensin-II activity. Reduction of vascular endothelium in response to appropriate stimuli is the main feature of endothelial dysfunction (8).…”
Section: Introductionmentioning
confidence: 99%